PENGARUH PEMBERIAN MACAM HORMON DAN KONSENTRASI TERHADAP PERKECAMBAHAN KOPI LIBERIKA - Jourdan Alexander Niagara; Agus Sulistyono; Juli Santoso (UPN VETERAN JAWA TIMUR, 2018)
Coffee seeds are generally difficult to germinate with long dormancy time, this is an important aspect in this study to the response and use of hormones as stimulants grow for the seedling process of liberica coffee beans to quickly germinate. This study used two factors, it is hormone and concentration as the basic concept for coffee seed with giving treatment a mechanism soaked using hormones with different concentrations. Hormones as growth stimulants (ZPT) as the basis of the germination stimulation process. Hormones used for this study are the hormones GA3 / Giberelin, IAA / Auksin and BAP/Cytokinin. Hormonal solutions are of course not independent of concentration or normality in the solution, therefore the study applies 3 levels of concentrations including 250ppm, 500ppm and 750ppm as a combination of hormones and normality to test the viability of germination, plant heights, stem diameters, wet weights of the plant, and root length as the observation parameter. Furthermore, the value of the observation will be analyzed by using anova (LSD) 5% confidence level. After 5% of treatment result (LSD), the best effect was obtained from the treatment of combination of GA3 hormone with 250ppm concentration of 1.5273 (cm) and this treatment was the best for GA3 hormone with plant height is 2,627 (cm).